A Rare Case of Non-IUD-Related Chronic Endometritis caused by Actinomyces Bacteria in a Postmenopausal Woman: A Case Report - González-García, Stephanie M.; Pastrana-Arroyo, Manuel J.; Medina-Parrilla, Eduardo; González, Anarda; Martín, José (Puerto Rico Health Sciences Journal, 2022)
Pelvic actinomycosis is a rare condition, usually associated with intrauterine device (IUD) use. Its clinical presentation may vary from being asymptomatic to the mimicking of pelvic malignancy; it has been described as one of the most misdiagnosed diseases. A 78-year-old woman without a history of IUD use, arrived at our clinic complaining of chronic and intermittent postmenopausal bleeding associated with lower pelvic pain. An endometrial curettage was performed, and endometritis (caused by Actinomyces) was identified. Treatment with intravenous piperacillin and tazobactam for 7 days, followed by 6 weeks of oral ampicillin, daily, decreased the bleeding and the pain. Although rare, it is important to consider Actinomyces-related endometritis as a differential diagnosis in cases of elderly woman with postmenopausal bleeding and without a history of IUD use.